PENGARUH CASH TURNOVER DAN WORKING CAPITAL TURNOVER TERHADAP KINERJA KEUANGAN DIMEDIASI PROFITABILITAS PADA “PT .MEKAR KINANTI DAN LINTANG KEJORA” SEMARANG PERIODE TAHUN 2013 – 2017 - Patricia Dhiana Paramita (Jurnal Ekonomi dan Bisnis Kontemporer, 2019)
Financial performance is very important for a company. To see the company's financial performance can be seen from the level of profitability achieved for thecompany in a certain period of time. The profit of a company can be seen from the cashturnover and the company's working capital turnover, as well as "Mekar Kinanti andLintang Kejora" Semarang. The purpose of this research is to determine the effect ofcash turnover and working capital turnover partially on profitability and companyperformance and to determine whether profitability mediates the effect of cash turnoverand working capital turnover on the company's financial performance. The data source used in this research is secondary data, which relates to theobject of research, namely "PT. Mekar Kinanti and Lintang Kejora " Semarang, whichis a company engaged in making garments. in the form of financial data from 2013 to2017. The analysis techniques used are gradual linear regression, classic assumptiontest, goodness of fit test and path analysis. Based on the results of calculations, it can be seen that cash turnover and workingcapital turnover partially have a positive and significant effect on profitability and thecompany's financial performance and profitability have a positive and significant effecton the company's financial performance. Profitability does not mediate the effect ofcash turnover and partial working capital turnover on the company's financialperformance. It is better for management "PT. Mekar Kinanti and Lintang Kejora "Semarangseeks to increase cash turnover and working capital turnover in order to have a positiveimpact on profitability, so that it can improve financial performance " PT. MekarKinanti and Lintang Kejora "Semarang.Keywords: cash flow, working capital turnover and cash turnover, profitability and financial performance